Analisis Dampak Ekonomi Dan Sosial Pada Lingkungan Hidup Terhadap Usaha Ikan Lele di Desa Basanah Dalam Prespektif Hifd Al Biah - Taufiq, Muhammad Fahrud; Yanti, Natasya Dwi; Rahman, Abdur (FEB Universitas Maritim Semarang, 2025)
This study aims to analyze the economic and social impacts within the environmental context on the sustainability of catfish farming in Basanah Village. Environmental issues such as water quality, land availability, and land-use changes have significantly affected aquaculture practices. Moreover, the social dynamics of the surrounding community, including patterns of cooperation, public perception of catfish farming, and economic impacts on farmers’ income and welfare, are central to the investigation. This research employs a descriptive qualitative approach through field observations, in-depth interviews, and documentation involving local farmers, community leaders, and relevant stakeholders. The findings reveal that economic aspects, such as production cost efficiency and income improvement, are highly dependent on stable environmental conditions and strong social support. Conversely, environmental degradation and weak social participation hinder business development. Therefore, participatory-based policies integrating sustainable environmental management with the strengthening of local socioeconomic capacities are urgently needed. This study offers a significant contribution as a foundation for formulating empowerment strategies for environmentally and socially-based small-scale aquaculture enterprises at the village level.